Alpha-Amylase Activity of Lactic Acid Bacteria Isolated from Different Fermented Products: Characterization of Latilactobacillus Curvatus Y2-1B Amylase - Turkay, Şeyda Nur; Karaman, Kevser; Bekiroglu, Hatice (My University, 2025)
In this study, ninety-one lactic acid bacteria isolates (LAB) were obtained from different fermented products and their ability to produce ?-amylase was qualitatively examined using starch added medium. Of the LAB isolates, 75 LABs were qualitatively confirmed to be amylase positive, and 20 LABs in total were found to exhibit significant ?- amylase production ability. Quantitative tests of ?-amylase enzyme activity were then conducted and enzyme activity values for LABs were found in the range of 1.283 U/mL to 13.670 U/mL. Then, 3 LAB isolates (P4-2B, Y2-1B, S1-2B) were selected and identified by genotypic methods. The enzyme from the Latilactobacillus curvatus Y2-1B isolate was partially purified, and activity tests were conducted to ascertain the impact of pH, temperature, and cations. The lowest enzyme activity was found to be 0.554 U/mL at pH 9 and 0.694 U/mL at pH 6 as the highest value (p<0.05). On the other hand, the purified enzyme formed a band of approximately 40 kDa in SDS-PAGE while the presence of the genes amy was examined and approved. It was concluded that selected LAB isolates may be useful in industrial biotechnology and microbial enzyme industry due to their ?-amylase enzyme activity.
Keywords: Thermostable; amylase; Latilactobacillus curvatus; specific activity